Inhibitor Effect of Antioxidant Flavonoids Quercitin, and Capsaicin in Mast Cell Inflammation. (May 2013) - Shaik-Dasthagirisaheb, Y.B.; Varvara, G.; Murmura, G.; Saggini, A.; Caraffa, A.; Antinolfi, P.; Tetè, S.; Rosati, M.; Cianchetti, E.; Toniato, E.; Speranza, L.; Pantalone, A.; et al.
Mast cells are essential not only for allergies but also for innate and acquired immunity, autoimmunity and inflammation, and they are recognized as a new type of immunoregulatory cells capable of producing different cytokines. Natural compounds have long been recognized to possess anti-inflammatory, antioxidant and anticancergenic activity. Quercitin is an inhibitor for mast cells and is a potent antioxidant, cytoprotective and anti-inflammatory compound and has a negative effect on intracellular regulator signal events initiated by FceRI receptor cross-linking and other activating receptors on mast cells. These observations candidate quercitin as a therapeutic compound in association with other therapeutic molecules. Capsaicin is a compound derived from peppers, especially capsicum, and is involved in stimulating circulation aiding digestion and relieving pain. Capsaicin receptor sub type I (VRI) is expressing in neurons and is present in a number of brain nuclei and in non-neuronal tissues, mediating inflammatory response. Capsaicin is involved in migraine, allergic symptoms, arthritis pain and gastric secretion. In this paper we review the biological effects of quercitin and capsaicin.